Transformation of vocational education services and innovative management mechanisms in the digital economy - Sherzod Toshpulatov (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Abstract. This thesis analyzes the theoretical foundations of the transformation of vocational education services in the digital economy and the issues of improving innovative management mechanisms. In the context of modern economic development, the widespread introduction of digital technologies requires new approaches to the organization and management of vocational education services at all stages of the education system, in particular, in this regard. In this regard, the thesis scientifically substantiates the relevance of digitizing educational services, their platformization and integrating innovative technologies into management processes.